Electric Pulp Test Threshold Responses in Healthy Mature Permanent Teeth: Electric Pulp Test Threshold Responses in Healthy Teeth - Noor, Razia; Aslam, Shuja; Memon, Aosaf Anwar; Ali, Irum; Zaidi, Hasan Afaq; Ali, Ahsan (Pakistan Journal of Health Sciences, 2024)
Electric pulp testers assess only the neural component of pulp sensibility in dental practice, while vascular status is evaluated with laser Doppler flowmeters and pulp oximeters, which are more reliable for determining vitality in traumatic teeth. Objective: To determine the accuracy of the electric pulp test in healthy mature permanent teeth. Methods: This cross-sectional study was conducted at the Liaquat University of Medical and Health Sciences Jamshoro by consecutive sampling on 220 participants aged 18-35, who had healthy, mature permanent central incisors, canines, first premolars, and first molars, with no history of cardiac pacemakers and metallic restorations. Teeth were isolated, dried, and tested with a COXO C-Pulse electric pulp tester using toothpaste as a conducting medium. Threshold responses were recorded at increasing currents, with each tooth tested twice to determine the mean value. Accuracy was assessed using additional metrics post-therapy. Chi-square tests were employed to compare accuracy across gender and age groups, with significance set at p<0.05. Results: The mean age of the patients was 25.55 ± 5.41 years. 132 (60%) subjects were female, 88 (40%) subjects were male in this study. Accuracy of the electric pulp test in healthy mature permanent teeth was detected in 181 (82.3%) subjects in this study. Conclusion: It was concluded that the electric pulp tester method seems to be a reliable way to evaluate how sensitive the live nerve tissue inside a tooth is for healthy permanent teeth that have fully formed.